2004
DOI: 10.1007/s00011-004-1251-7
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of arginine vasopressin in endogenous central histamine-induced reversal of critical haemorrhagic hypotension in rats

Abstract: AVP, acting via V(1a) receptors, is involved in endogenous central histamine-induced reversal of critical haemorrhagic hypotension in rats.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
46
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 31 publications
(51 citation statements)
references
References 43 publications
5
46
0
Order By: Relevance
“…Indeed, we previously showed in dogs that activation of mast cells located in the ME stimulates the HPA axis via histamine released within the CNS, either in response to an antigenic challenge following passive sensitization by IgE (41) or in response to C48/80 given into the V III (42). Here, in a study designed to examine whether brain mast cells might be the source of the central histamine that is known to participate in the regulation of both renin (5,30,33,44,55) and ADH (2, 7, 15, 57) secretion, we first showed that an intracerebroventricular administration of C48/80 evokes a marked increase in renin secretion and significant increases in plasma ADH and Epi.…”
Section: Discussionmentioning
confidence: 94%
See 4 more Smart Citations
“…Indeed, we previously showed in dogs that activation of mast cells located in the ME stimulates the HPA axis via histamine released within the CNS, either in response to an antigenic challenge following passive sensitization by IgE (41) or in response to C48/80 given into the V III (42). Here, in a study designed to examine whether brain mast cells might be the source of the central histamine that is known to participate in the regulation of both renin (5,30,33,44,55) and ADH (2, 7, 15, 57) secretion, we first showed that an intracerebroventricular administration of C48/80 evokes a marked increase in renin secretion and significant increases in plasma ADH and Epi.…”
Section: Discussionmentioning
confidence: 94%
“…In the view of the increases in renin and ADH secretions evoked by central mast cells, previous studies have shown that the concentration of histamine in the brain increases during hemorrhage (30) or dehydration (33) and that central histamine participates in hemorrhage-induced renin secretion (29,30,44). Furthermore, manipulations that increase the central histamine content [e.g., an administration either of histamine itself (29) or of a histamine N-methyl transferase inhibitor (30) into the V III ] rescue animals from critical hemorrhagic hypotension by increasing MAP and HR via an activation of the reninangiotensin system (30) and may be via release of ADH, too.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations